The problem of the authenticity of Al-Ghazali’s work and its relation to the nature of his sufism - Kamarudin Haji Salleh (Penerbit Universiti Kebangsaan Malaysia, 2000)
This article attempts to disclose the problem of the authenticity of some of Imam al-Ghazali’s works and its relation to the nature of his view on sufism. Western writers, for instance Watt, Macdonald, Goldziher and others disputing over some of books using al-Ghazali’s name such as Mishkat al-Anwar, al-Risalah al-Laduniyyah, Rawdah al-Talibin and others. Their arguments are based on the inconsistencies of al-Ghazali’s idea on sufism (including theoretical and philosophical sufism) in those books with his general attitude towards sufism